2020
DOI: 10.1093/biolinnean/blaa186
|View full text |Cite
|
Sign up to set email alerts
|

The influence of domestication, insularity and sociality on the tempo and mode of brain size evolution in mammals

Abstract: The ability to develop complex social bonds and an increased capacity for behavioural flexibility in novel environments have both been forwarded as selective forces favouring the evolution of a large brain in mammals. However, large brains are energetically expensive, and in circumstances in which selective pressures are relaxed, e.g. on islands, smaller brains are selected for. Similar reasoning has been offered to explain the reduction of brain size in domestic species relative to their wild relatives. Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
(62 reference statements)
1
16
1
Order By: Relevance
“…Notably, evolutionary rates in domesticates have been shown to be both faster than (Castaglione et al. 2021), and the same as (Geiger et al. 2018), wild mammals.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, evolutionary rates in domesticates have been shown to be both faster than (Castaglione et al. 2021), and the same as (Geiger et al. 2018), wild mammals.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, recent studies show that the role of allometry in determining brain variables should be revised, but its significant influence on brain studies is obvious. Repeated analyses with different methods have even confirmed the original conclusions made from allometric approaches [Finlay et al, 2011;Castiglione et al, 2021]. Taxon-specific brain/body allometry is still widely acknowledged and gives insights into the development of brain (parts) size [Willemet, 2013].…”
Section: Domestication and Evolutionmentioning
confidence: 74%
“…Therefore, the reduction in brain size is not a regrettable degeneration, but rather an optimal adaptation to the actual conditions. Large brains are energetically expensive, and in circumstances in which selective pressure is relaxed, e.g., in a man-made environment, selection is for smaller brains [Castiglione et al, 2021]. Given the worldwide distribution and numbers of domestic animals, there is no doubt that they are very successful in their ecological niche (man-made).…”
Section: Domestication and Evolutionmentioning
confidence: 99%
“…of extant dog spp. (Canidae) insular dwarf canid has normal relative brain size Sardinia, Italy comparative analysis of brain size [ 96 ] Minorcan giant rabbit ( Nuralagus rex ), compared to extant rabbit species (Leporidae) Late Neogene insular giant had relatively small brain; especially sense-dependent areas are small Minorca, Balearic Islands, Spain absence of predators; limited energy availability comparative analysis of brain size [ 97 ] 426 mammalian species no effect of insularity on relative brain size islands worldwide mainland sites throughout the world poor dietary resources on islands natural selection for smaller brains comparative analysis of brain size [ 98 ] dodo ( Raphus cucullatus ) compared to nine spp. of pigeons (Columbiformes) endocranial volume not smaller than expected from pigeon allometry Mauritius allometric analysis [ 99 ] Rodrigues Island giant owl (Otus murivorus ), compared to 10 extant spp.…”
Section: The Current Evidence For a Behavioural Component To The Isla...mentioning
confidence: 99%
“…[ 95 ], the Sardinian dhole ( Cynotherium sardous ) [ 96 ], or even the long-thought-dim dodo ( Raphus cucullatus ) [ 99 ]. Third, recent comparative studies on extant mammals [ 98 ] and crows and ravens [ 102 ] found no effect of insularity on relative brain size. A meta-analysis of over 1900 species of birds even suggests a tendency towards larger brains in insular species.…”
Section: The Current Evidence For a Behavioural Component To The Isla...mentioning
confidence: 99%